Beyond Symbolic Government Branding: An Integrative Model of Public Trust in Indonesia's Digital Building Certification Services (SLF) - Florentina Ratih Wulandari; Dwi Putranto Riau; Abdurrahman Rahim Thaha (FOUNDAE (Foundation of Advanced Education), 2026)
Background: The digitalization of public regulatory services does not automatically strengthen public trust, participation, or regulatory compliance. In Indonesia, the Building Management Information System (SIMBG) supports the Certificate of Occupancy (SLF) process, yet certification outcomes remain influenced by users’ service experiences, communication quality, institutional credibility, and broader administrative conditions. This study examines government branding as a substantive service-based mechanism rather than merely a symbolic communication strategy. Methods: An explanatory sequential mixed-methods design was employed. The quantitative phase involved 300 SIMBG users from Sidoarjo, Semarang, and Bandung selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The qualitative phase used semi-structured interviews and document analysis to explain and contextualize the quantitative findings. Findings: Public participation showed the strongest positive relationship with SIMBG adoption (β = 0.766), followed by communication quality (β = 0.562). SIMBG adoption was also strongly associated with SLF ownership (β = 0.712). Qualitative findings indicated that procedural transparency, communication clarity, responsive assistance, and consistency between government messages and actual service delivery shaped perceptions of institutional credibility. Technical assessment costs, limited availability of qualified experts, document revisions, and other non-platform requirements remained important barriers to certification completion. Conclusion: Effective digital building certification depends not only on technological availability but also on credible government-user relationships and a supportive certification ecosystem. Government branding becomes substantively credible when messages of convenience, transparency, and professionalism are reinforced by actual service performance. Novelty/Originality: This study positions SIMBG as a digital service-based brand touchpoint linking participation, communication quality, platform adoption, SLF completion, and public value.